NARASI PENDERITAAN DAN KESABARAN NABI DALAM YAKOBUS 5:10: IMPLIKASI TEOLOGIS BAGI KEPEMIMPINAN GEMBALA JEMAAT - Paulus Kunto Baskoro; Anon Dwi Saputra (Manna Rafflesia, 2026)
Pastors are often perceived as problem solvers, yet they are ordinary individuals carrying a sacred calling that demands complete spiritual exemplary. A crucial, often overlooked focus is the perseverance in enduring unexpressed internal suffering. This descriptive qualitative study, utilizing a library research method, aims to analyze the relevance of James 5:10 for contemporary ecclesiastical leadership. Through the exegesis of the text "Take the prophets as an example of suffering and patience," it is found that the suffering of the prophets serves as an essential prototype of exemplary leadership. The research findings indicate that patience (makrothumia) in suffering constitutes a spiritual authority that strengthens the congregation. In conclusion, the effectiveness of pastoral care is measured by the pastor's capacity to persistently manage emotional suffering without compromising integrity. The novelty of this research lies in the context of "unexpressed emotional suffering." This article offers a perspective that emotional resilience and internal patience are essential instruments of transformative leadership in modern ecclesiology.